Intestinal Obstruction Changing Etiological Trends - Adnan Ali Qureshi, Jahangir Sarwar Khan (Journal of Rawalpindi Medical College, 2008)
Background: To describe clinical presentation, etiology, and management of patients presenting with intestinal obstruction. Method: From 6th September 2004 to 6 September 2005, 50 patients with provisional diagnosis of intestinal obstruction were admitted from emergency room of Rawalpindi General Hospital. All patients were initially assessed after resuscitation in emergency room. The decision, to operate or manage conservatively, was taken by a consultant. The clinical diagnosis was matched with per-operative findings and histopathology reports. Results: Of the total 50 patients, 42 were males and 8 were female. The age distribution varied from 15 years to 70 years. Mean age was 41.7 ± 13.6.Commonest symptom with which the patients presented was generalized abdominal pain. Most common sign was tachycardia, present in 49 patients. Most common etiology leading to intestinal obstruction was obstructed inguinal hernia in 22 followed by post operative adhesions in 12 patients. Conclusion: Obstructed inguinal hernia is the most common etiology of intestinal obstruction. Early diagnosis and surgical intervention is required to decrease gut ischemia leading to increased morbidity in patients